Communication of Community Organizations (Ormas) in Mitigating Earthquake Victims in Cianjur - Khumaedi, Teddy; Irawan, Mira Septi; Ismail, Taufik (State Islamic Institute of Bone, Indonesia, 2023)
The location of the epicenter of the earthquake is located on land in the Cianjur Regency, West Java Province. According to geographical data, Cianjur Regency is located at coordinates 1060 42' - 1070 25' East Longitude and 60 21' - 7 0 25' South Latitude, with an area of 361,434.98 hectares. The existence of the Cugenang Fault fault triggered this earthquake because it is an active fault, so it is prone to shifts. This causes the area traversed by the Cugenang Fault to become a dangerous zone for the establishment of permanent buildings. This study shows that the damage in the Cianjur Regency area was caused by the quality of the buildings, asymmetrical construction structures and the selection of poor quality construction materials.